Extraordinary thermoelectric performance, thermal stability and mechanical properties of n-type Mg3Sb1.5Bi0.5 through multi-dopants at interstitial site. (October 2022) - Jiang, Feng; Feng, Tao; Zhu, Yongbin; Han, Zhijia; Shu, Rui; Chen, Chen; Zhang, Yiwen; Xia, Chengliang; Wu, Xinzhi; Yu, Hulei; Liu, Chengyan; Chen, Yue; et al.
Abstract: Mg3 Sb2 -based thermoelectric materials have attracted much interest since the discovery of their excellent n-type thermoelectric performance with excess Mg content and proper dopant. Herein, we proposed a doping diagram for Mg3 Sb2 -based material in a binary parameters space of electronegativity difference and atomic radius difference of extrinsic elements with Mg atom. Based on this doping diagram, we designed a multiple interstitial doped TM x :Mg3 Sb1.5 Bi0.5 (TM = CrMnFeCoCu) material, and achieved a high dimensionless figure of merit value of 0.76 at room temperature and 1.83 at 500 °C, respectively. The multiple interstitial dopants significantly suppress the formation of Mg vacancy, which is of great importance in protecting the electrical transport channel and improving the thermal stability. Besides, the mechanical properties are also enhanced due to the random distribution of elements in the matrix, impeding the migration of dislocations. Our work verifies the benefits of maximized sub-lattice disordering through the multi-elements doping strategy in the Mg3 Sb1.5 Bi0.5 material. Graphical abstract: Image 1 Highlights: A doping diagram is constructed to select proper dopants for Mg3 Sb2 -based material. A high power factor of ∼2799 μW m −1 K −2 and a promising ZT of 0.76 is achieved at room temperature. The thermal stability and mechanical properties of Mg3 Sb2 -based material are enhanced by multiple interstitial dopants.